Sandalwood fragrance biosynthesis involves sesquiterpene synthases of both the terpene synthase (TPS)-a and TPS-b subfamilies, including santalene synthases - Jones, C.; Moniodis, J.; Zulak, Katherine; Scaffidi, A.; Plummer, J.; Ghisalberti, E.; Barbour, E.; Bohlmann, J. (2011)
Sandalwood oil is one of the worlds most highly prized fragrances. To identify the genes and encoded enzymes responsible for santalene biosynthesis, we cloned and characterized three orthologous terpene synthase (TPS) genes SaSSy, SauSSy, and SspiSSy from three divergent sandalwood species; Santalum album, S. austrocaledonicum, and S. spicatum, respectively. The encoded enzymes catalyze the formation of a-, ß-, epi-ß-santalene, and a-exo-bergamotene from (E,E)-farnesyl diphosphate (E,E-FPP). Recombinant SaSSy was additionally tested with (Z,Z)-farnesyl diphosphate (Z,Z-FPP) and remarkably, found to produce a mixture of a-endo-bergamotene, a-santalene, (Z)-ß-farnesene, epi-ß-santalene, and ß-santalene. Additional cDNAs that encode bisabolene/bisabolol synthases were also cloned and functionally characterized from these three species. Both the santalene synthases and the bisabolene/bisabolol synthases reside in the TPS-b phylogenetic clade, which is more commonly associated with angiosperm monoterpene synthases. An orthologous set of TPS-a synthases responsible for formation of macrocyclic and bicyclic sesquiterpenes were characterized. Strict functionality and limited sequence divergence in the santalene and bisabolene synthases are in contrast to the TPS-a synthases, suggesting these compounds have played a significant role in the evolution of the Santalum genus.